Kohesivitas Suami Istri Dalam Mewujudkan Keharmonisan Rumah Tangga: Studi Kasus di Gunung Kidul Yogyakarta - Suciati Suciati (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2013)
Each couple must have longed for harmony in the household, but many of them decide to divorce. The issue is not resolved for the sake of the problems cause conflict.This happens when couples are no longer uphold openness and trust. This study raised the marital cohesion in the area of Gunung Kidul Yogyakarta, considering this region occurred in the case of divorce due to lack of harmony in the marital relationship. Data was collected through in-depth interviews with three pairs of husband and wife. The study concluded that the three couples showed cohesiveness characterized by a relatively high intensity of togetherness, the role of head of the family stay on her husband, satisfaction with the solutions generated and the defense their family name.